Recent development in understanding the role of lipids in cartilage lubrication - Yumeng Xue; Xiaolian Niu; Jin Zhou; Lizhen Wang; Yubo Fan (Friction)
Lubrication deficiency in articular cartilage (AC) triggers irreversible and progressive degradation of AC, termed osteoarthritis (OA). Bio-lubrication-based strategies have been proposed as effective ways to restore temporary cartilage lubrication for OA postponement or even OA healing. The design of lubricants has inspired an exploration of the reasons behind the low friction in cartilage and the components responsible for the lubrication function in cartilage. Recently, lipids, as emerging lubrication components in AC, have been extensively studied and confirmed to play essential roles in maintaining cartilage lubrication. This review brings forward the main challenges of establishing a satisfactory functional articular cartilage biomaterial with sufficient lubrication from the perspectives of the complexity of physiology and microenvironment of osteochondral tissue. Next, we comprehensively discuss lubrication models of AC, including the lubrication mechanism of AC, OA associated with lipids, lipid lubrication mechanism and application, and the synergistic effects of phospholipids in lubrication. In particular, we highlight the advantages and application of lipids and their derivatives in lubrication. Finally, we analyze the future prospects of lipid-based biomaterials to achieve the perfect treatment of OA. This comprehensive and instructive review can provide deep insights into our current understanding of lipids and lubrication-related diseases.